2013
DOI: 10.11622/smedj.2013005
|View full text |Cite
|
Sign up to set email alerts
|

Coronary computed tomography angiography with prospective electrocardiography triggering: a systematic review of image quality and radiation dose

Abstract: Singapore Med J 2013; 54(1) : 15 R ev iew A r tic le INTRODUCTIONCoronary computed tomography angiography (CCTA) has been widely used as a valuable diagnostic imaging modality for the noninvasive assessment of coronary artery disease (CAD). It has become a reliable and accurate modality to assess the coronary arteries of patients with suspected CAD.(1) Previous studies have found that retrospective electrocardiography (ECG)-gated CCTA provides high sensitivity (range 86%-99%) and specificity (range 89%-100%) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…There was no significant difference in the IQ between double low- and routine-dose groups, and the image qualifying rate of these 2 groups were higher than the international level (96.8%). [ 20 , 21 ] In the routine-dose group, incorrect diagnosis was due to the dense calcification in 18 segments (64.3%), which was the cause in 17 segments (63%) for the double low-dose group. Obviously, dense calcification represented the primary cause for misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the IQ between double low- and routine-dose groups, and the image qualifying rate of these 2 groups were higher than the international level (96.8%). [ 20 , 21 ] In the routine-dose group, incorrect diagnosis was due to the dense calcification in 18 segments (64.3%), which was the cause in 17 segments (63%) for the double low-dose group. Obviously, dense calcification represented the primary cause for misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…50 Radiation dose and hence repeated CTCA assessment is acceptable with the latest generation of CT-scanners. 60 In children, CTCA may result in a median effective dose of only 1 mSv when performed by 128-slice dual source CT. 61 CTCA on the latest generation of CT-scanners also enables image acquisition with a high temporal resolution that allows for application in new- borns and children without sedation. 61 If CTCA is not available, one should consider referring patients to the nearest center with such scanner.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…A systematic review by Menke et al reported a pooled effective dose of 3.5 mSv with prospective triggering, a factor of 3.5 lower than the pooled effective dose of 12.3 mSv with retrospective gating with comparable CCTA image quality and diagnostic accuracy [ 31 ]. Furthermore, prospective ECG-gating allows extra low-dose cardiac imaging with high sensitivity, specificity, negative predictive value, positive predictive value, and accuracy for detecting CAD [ 32 ]. This method, however, reaches its limits with patients with severe arrhythmia since it relies on the prediction of the patient’s next cardiac cycle.…”
Section: Scan Modementioning
confidence: 99%